PROBLEMS OF BILINGUISM AND INTERFERENCE (Western European Journal of Linguistics and Education, 2024)
The article gives an idea of the phenomenon of interference and its specificity, the different assessments of this phenomenon by linguists. Feedback and conclusions on the study of the phenomenon of interference in the context of multilingualism at the language level and the formation of new areas are presented